Financial risk manager handbook plus test bank : FRM Part I/Part II - Jorion, Philippe (Hoboken, N.J. : J. Wiley & Sons, 2011)
The handbook summarises the core body of knowledge for financial risk managers, covering such topics as; market,credit,operational, and integrated risk management, quantitative methods investment management and hedge fund risk.
Includes index.
uaj 29/04/13
Loans
Keywords: Financial risk management; Risk management; Corporations